Iatrogenic Esophageal Perforation in Patients with Head & Neck Cancer: Evaluation of the SEER-Medicare Database - Ghogomu, Nsangou T (2010)
OBJECTIVE: 1. Determine rate of iatrogenic esophageal perforation in head and neck cancer patients. 2. Identify risk factors for perforation. 3. Determine effect of perforation on mortality. STUDY DESIGN: Secondary data analysis SETTING: SEER-Medicare linked database SUBJECTS AND METHODS: Patients diagnosed with squamous cell carcinoma of the upper aerodigestive tract between January 1995 and December 2002 who underwent esophagoscopy were included. Primary outcome was rate of iatrogenic esophageal perforation. Secondary outcomes included identification of risk factors for perforation and effect of perforation on mortality. Logistic regression analysis and chi-square test were used to evaluate risk factors and 30-day mortality. RESULTS: There were 152 perforations in 126 patients, for a rate of 2.70% (95% C.I. 2.28 to 3.20) per patient (N=4,659) and 1.44% (1.21 to 1.67) per esophagoscopy (N=10,529). Odds of perforation were increased in patients with cancer of the pharynx (OR 4.49, 1.82 to 11.08), pyriform sinus (OR 5.00, 2.10 to11.93), and larynx (OR 3.39, 1.57 to 7.34), and those who underwent both surgery and radiation (OR 1.75, 1.12 to 2.74). Each esophagoscopy increased odds of perforation by 22% (17 to 28). Compared to diagnostic esophagoscopy, perforation was 2.9 times (1.77 to 4.69) more likely when dilatation was performed. 30-day post-perforation mortality was 7.1%, a 3% absolute increase (−1.5 to 7.5) over the post-esophagoscopy rate in patients without perforation. CONCLUSION: Head and neck squamous cell carcinoma patients are a high-risk population for iatrogenic pharyngoesophageal perforation. Perforation is related to esophagoscopy frequency and type, tumor location, and use of multi-modality therapy.